Acyl‐Directed ortho‐Borylation of Anilines and C7 Borylation of Indoles using just BBr3. Issue 43 (12th September 2019) - Iqbal, Saqib A.; Cid, Jessica; Procter, Richard J.; Uzelac, Marina; Yuan, Kang; Ingleson, Michael J.
Abstract: Indoles are privileged heterocycles found in many biologically active pharmaceuticals and natural products. However, the selective functionalization of the benzenoid moiety in indoles in preference to the more reactive pyrrolic unit is a significant challenge. Herein we report that N‐acyl directing groups enable the C7‐selective C−H borylation of indoles using just BBr3 . This transformation shows some functional‐group tolerance and notably proceeds with C6 substituted indoles. The directing group can be readily removed in situ and the products isolated as the pinacol boronate esters. Acyl‐directed electrophilic borylation can be extended to carbazoles and anilines with excellent ortho selectivity. 4‐amino‐indoles are amenable to this process, with acyl group installation and directed electrophilic C−H borylation enabling selective formation of C5‐BPin‐indoles. Abstract : B‐directed : Acyl‐directed electrophilic C−H borylation provides access to novel C5 and C7 borylated indoles using just BBr3 as the borylating agent via the formation of six‐membered boracycles.